A guide to the Reservoirs Act 1975 (Thomas Telford, 2000)
This publication provides guidance on the application of the Reservoirs Act 1975, reflecting the current views and practices of the dam engineering profession. It aims to encourage high standards of safety and promote the proper application of the act by all parties involved.
At foot of title page: DETR.
Keywords: Great Britain. -- Reservoirs Act 1975.; Reservoirs -- Law and legislation -- Great Britain.; elektronické knihy; electronic books